2023
DOI: 10.1111/dpr.12678
|View full text |Cite
|
Sign up to set email alerts
|

The governance shock doctrine: Civic space in the pandemic

Abstract: Motivation: Emergencies heighten societies' need to be governed. Accordingly, the COVID-19 pandemic put systems of public governance under severe pressure across the globe. Civic freedoms were widely curtailed for public health reasons. Scarce resources needed to be allocated swiftly, with little opportunity for debate. Purpose: In settings characterized by authoritarianism, violent conflict, and restricted civic space, relations between governments, civil society, and citizens at best tend to be fragile and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…On the OECD Fragility Index all are ranked as highly fragile in terms of security issues, meaning threats of violence still loom large (OECD, 2020). And each country has experienced limited civic space, which worsened further under COVID‐19 (McGee, 2023). In 2021, the CIVICUS Monitor, which measures civic space, characterized Mozambique, Nigeria, and Pakistan all as “repressed,” while Myanmar was downgraded from “repressed” the previous year to “closed” (CIVICUS, 2021).…”
Section: The Settings and The Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…On the OECD Fragility Index all are ranked as highly fragile in terms of security issues, meaning threats of violence still loom large (OECD, 2020). And each country has experienced limited civic space, which worsened further under COVID‐19 (McGee, 2023). In 2021, the CIVICUS Monitor, which measures civic space, characterized Mozambique, Nigeria, and Pakistan all as “repressed,” while Myanmar was downgraded from “repressed” the previous year to “closed” (CIVICUS, 2021).…”
Section: The Settings and The Approachmentioning
confidence: 99%
“…Research on closing civic space under COVID-19 found that, even as civic space grew even more constricted, such groups still played vital roles, often shifting to new areas of focus made more salient by the pandemic, such as health, livelihoods, or education (McGee, 2023). Across the countries, professional associations of doctors and nurses demanded greater protection and delivery of health services.…”
Section: Ngo-led Advocacymentioning
confidence: 99%
“…The COVID‐19 pandemic has further exacerbated these tendencies of simultaneous repression and polarization (McGee, 2023). In Nigeria, A4EA research suggested that:
the shoot‐at‐sight directives to security operatives to shoot any person that tries to escape from quarantine and isolation centres, deploying maximum force including military action to enforce compliance with safety protocols such as wearing of face masks, social distancing and ban on public gatherings—compounded by the overzealous conduct of security forces during the lockdown evince how securitized emergency measures are causing unwarranted fatalities, violating human rights and shrinking the civic space (Ibezim‐Ohaeri & Ibeh, 2020, p. 11).
At the same time, civic space is restricted selectively—it is open for those advancing identity‐based polarization agendas: for example, the Pakistan government was “unwilling, or unable to rein in religious gatherings and protests during the lockdown” (Khan et al, 2020, p. 9).…”
Section: What Are the Impacts Of Increased Contestation On Accountabi...mentioning
confidence: 99%
“…Their outlook and behaviour reflect their coping and resilience mechanisms rather than challenging powerful actors to meet their needs. This is not to say that people are inert; people do undertake a range of political actions to express their discontent through cultural voice, political protest, or formal electoral processes (see Gaventa, 2023; Nazneen, 2023; McGee, 2023). Indeed, the focus of the A4EA research programme was on instances of social and political action which did occur, albeit in unexpected ways and places (Anderson et al, 2022; Joshi, 2019).…”
Section: What Are the Impacts Of Increased Contestation On Accountabi...mentioning
confidence: 99%
“…Continuing the theme of how citizens mobilize to make claims and express voice in difficult contexts, the article by McGee (2023), which largely focuses on civic space, repression, and centralization of authority tightened under COVID-19, also shows that even in such conditions, civic action remained strong, using a combination of strategies.…”
Section: Strategies and Repertoires For Claiming Accountabilitymentioning
confidence: 99%